Biological characteristics and genome-wide sequence analysis of endophytic nitrogen-fixing bacteria Klebsiella variicola GN02. Issue 1 (1st January 2019) - Lin, Biaosheng; Song, Zhaozhao; Jia, Yulei; Zhang, Yulong; Wang, Lifang; Fan, Jinling; Lin, Zhanxi
Abstract: The biological characteristics and genome-wide sequence analysis of highly efficient endophytic nitrogen-fixing bacteria Klebsiella variicola GN02 isolated from the roots of Pennisetum sinense Roxb. were studied by the combination of second-generation and third-generation sequencing techniques. The cell cultivation characteristics, microscopic morphological observation and infrared spectroscopic analysis of this GN02 strain were performed and its genome assembly, gene prediction and functional annotation, eggNOG/GO clustering analysis and co-linearity analysis were conducted through corresponding software. The results showed that the GN02 strain had the basic morphological characteristics of genus Klebsiella and it had the characteristic absorption peak of marker C-N group and the characteristic absorption peaks of carbonyl and amide groups in nitrogen-fixing bacteria. The GN02 genome size was 5, 599, 366 bp with GC content of 57.41%, 5, 261 ORF, 25 rRNA, 87 tRNA, 125 other ncRNA, 7 CRISPR repeats, and 54 GIs. Gene function annotations indicate that there were a large number of genes closely related to cellular nitrogen metabolism and the genes with high abundance are associated with amino acid metabolism. The genome-wide sequence has been submitted to the GenBank database under the accession number of CP31061. The basic characteristics of GN02 genome are similar to those of other K. variicola . Several strains of K. variicola have good co-linearity. The GN02 strain has a complete nitrogen-fixing gene group and 57 nitrogen-fixing genes have been identified.